Mathematical model of a motor-grader movement in the process of performing working operations. Issue 1 (November 2020) - Shevchenko, V; Chaplyhina, O; Pimonov, I; Reznikov, O; Ponikarovska, S
Abstract: The design features of a motor-grader help it perform a wide range of working operations, which puts it on a par with the main machines in the construction industry. Unlike other earth-moving machines, the motor-grader can perform work operations not only in a cyclic mode, but also in a continuous action mode. Considering these features, not only productivity should be addressed as the main indicator of the efficiency of this machine, but also the indicators of the quality of the working operations performed, in particular, the indicators of road-holding ability in the process of performing continuous working operations. The work has substantiated and developed a mathematical model of the motor-grader movement during working operations. This model makes it possible to predict the expected trajectory of the motor-grader on the basis of deterministic dependencies, which enables to assess the indicators of road-holding ability. The difference between the proposed model and the existing ones is the consideration of a two-stage mode of machine movement: plane motion at the first stage and rotational around the stop point at the second. When describing the external forces acting on the motor-grader, the differences in the formation of resistance forces on the blade during various working operations are taken into account.